ERP und SCM : Enterprise Resource Planning und Supply Chain Management in der Industrie - Kurbel, Karl (De Gruyter Studium, 2021)
Enterprise Resource Planning (ERP) and Supply Chain Management (SCM) are core tasks of every industrial company. In addition to the basics of ERP and SCM and the implementation of theoretical concepts in practical systems, the new edition deals with the latest developments in Industry 4.0 and the Internet of Things. Most business processes are handled with the help of an ERP system.